The fermentation characteristics of soy yogurt with different content of d-allulose and sucrose fermented by lactic acid bacteria from Kimchi - Kim, Hee Jin; Han, Myung Joo (Food science and biotechnology, 2019)
In this study, to understand whether d -allulose, an ultra-low calorie sweetener, was available in soy yogurt fermentation, we isolated Leuconostoc mesenteroides and Lactobacillus plantarum from kimchi and fermented in soymilk at various contents of d -allulose and sucrose. The lactic acid bacteria counts in soy yogurt had the highest range of 9.23–9.49 log CFU/g at 24 h fermentation and then decreased. At 48 h fermentation, the pH showed 4.31 and 4.52 in the samples containing 75% and 100% d -allulose as sweetener. DPPH radical scavenging activity showed a decreasing tendency as the amount of d -allulose increased. Soy yogurt samples containing d -allulose had higher scores in sweet taste, sour taste and overall preference in sensory evaluation. These findings suggest that d -allulose is beneficial for the development of a low calorie soy yogurt.